Tolerability of the capsaicin 8% patch following pretreatment with lidocaine or tramadol in patients with peripheral neuropathic pain: A multicentre, randomized, assessor‐blinded study. (24th March 2014) - Jensen, T.S.; Høye, K.; Fricová, J.; Vanelderen, P.; Ernault, E.; Siciliano, T.; Marques, S.
Abstract Background Application of the capsaicin 8% patch is associated with treatment‐related discomfort. Consequently, pretreatment for 60 min with anaesthetic cream is recommended; however, this may be uncomfortable and time consuming. Methods We conducted a multicentre, randomized (1:1), assessor‐blinded study in patients with peripheral neuropathic pain to assess tolerability of the capsaicin patch following topical lidocaine (4%) or oral tramadol (50 mg) pretreatment. The primary endpoint was the proportion of patients tolerating capsaicin patch application (ability to receive ≥90% of a 60‐min application). Numeric Pain Rating Scale (NPRS) scores were assessed before, during and after treatment. Results Overall, 122 patients were included (61 per arm). The capsaicin patch was tolerated by 121 patients. Tolerability of the capsaicin patch was similar following pretreatment with lidocaine and tramadol. Following patch application, pain levels increased up to 55 min (change from baseline of 1.3 for lidocaine and 1.4 for tramadol). After patch removal, tramadol‐treated patients experienced greater pain relief up to the end of day 1; in the evening, mean changes in NPRS scores from baseline were 0 for lidocaine and −1 for tramadol. Proportions of patients reporting increases of ≥2 NPRS points or >33% from baseline at one or more time point(s) on the day of treatment were similar between arms. Adverse event incidence was comparable between arms. Conclusions Capsaicin 8% patch tolerability was similar in the two arms, with comparable results for most secondary endpoints. Tramadol given 30 min before patch application should be considered as an alternative pretreatment option in patients receiving capsaicin patch treatment.